2021
DOI: 10.3390/su132313447
|View full text |Cite
|
Sign up to set email alerts
|

What Should Be Focused on When Digital Transformation Hits Industries? Literature Review of Business Management Adaptability

Abstract: How traditional industries adapt to the digital economy to achieve sustainable development has attracted scholars and practitioners. Exploring the concept of BMA (business management adaptability) can not only theoretically explain adaptive micro-operation mechanisms but can provide practical guidance for enterprises to form adaptability. To date, although a lot of effort is being spent on detecting the adaptive construction elements, refining the BMA to specific management levels, a comprehensive review combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 155 publications
0
1
0
Order By: Relevance
“…Correlational analysis demonstrated a significant positive relationship between identifying adaptive challenges behavior and digital transformation in these firms (r = 0.530, p < .05), aligning with prior research emphasizing the positive influence of work complexity, team collaboration, and experimentation on organizational outcomes. Notably, work complexity (Zhang et al, 2021), team collaboration (Costumato, 2021), and experimentation (Wong, 2020) have previously been found to have a positive impact on organizational outcomes. However, some studies reported weak associations for these factors (Audenaert et al, 2017;Bornay-Barrachina & Herrero, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlational analysis demonstrated a significant positive relationship between identifying adaptive challenges behavior and digital transformation in these firms (r = 0.530, p < .05), aligning with prior research emphasizing the positive influence of work complexity, team collaboration, and experimentation on organizational outcomes. Notably, work complexity (Zhang et al, 2021), team collaboration (Costumato, 2021), and experimentation (Wong, 2020) have previously been found to have a positive impact on organizational outcomes. However, some studies reported weak associations for these factors (Audenaert et al, 2017;Bornay-Barrachina & Herrero, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to Northouse (2019), adaptive leadership involves identifying and effectively addressing complex challenges, embracing change, and promoting innovation within an organization. One specific behavior of adaptive leadership is the identification of adaptive challenge, which encompasses work complexity, team collaboration, and experimentation practices by leadership (Wong, 2019;Zhang et al, 2021). While the importance of adaptive leadership behaviors in facilitating digital transformation is widely espoused by some scholars, others note the scant empirical research on this contemporary leadership style (Wamburu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital adaptability variable was related to the business management adaptability (BMA) concept that was used to theoretically explain adaptive micro-operation mechanisms and provide practical guidance for companies to adopt the digital economy to achieve sustainable development [50,51]. Furthermore, the costless signaling variable was linked to the existence of free internet and the constant expansion of the web with search engines continuously being used by people in their daily routines and found to be part of a complex and multi-faceted phenomenon considered difficult for companies to manage effectively [52].…”
Section: Methodsmentioning
confidence: 99%
“…For example, artificial intelligence (AI) can model, predict, and optimize the problems that arise throughout the entire construction process through data-driven methods [8]. The second aspect is the process of organizational adaptation to digital transformation [21,22]. For example, the formal and informal organizational structures of large construction enterprises will be profoundly affected by digital technology [22], and enterprise digital transformation can enhance organizational resilience [23], etc.…”
Section: Introductionmentioning
confidence: 99%